Lunch-box dream eaudiobook - Abbott, Tony (Recorded Books Inc., 2012)
In this compelling novel, Golden Kite Award-winning children's author Tony Abbott explores Jim Crow laws and family strife from multiple perspectives. During the summer of 1959, Bobby and his family are visiting Civil War battlefields. Tempers flare as an accident cuts their trip short and forces them to return home by bus. On their journey, they witness a black family getting denied bus seats. In brief flashes of insight, young Bobby begins to question his assumptions about race. "Beautifully crafted and written."-Publishers Weekly, starred review